Test on the Antioxidant Activities of Methanol Extract of Bidara Leaves (Ziziphus spina-christi L.) using the DPPH Radical Immersion Method - Dwi Bagus Pambudi; Nuniek Nizmah Fajriyah; Vidiah Rizka Shalekhah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Bidara (Ziziphus spina-christi L.) is a tropical tree originating from Sudan in which it is commonly known as